Aortic remodeling and survival for chronic post dissection thoracoabdominal aneurysm following physician-modified endograft - Guangmin Yang, MD; Yuang Jiang, MD; Guangjin Gao, MD; Guangyan Wu, MD; Yepeng Zhang, MD; Min Zhou, PhD (JVS-Vascular Insights)
Objective: This study aimed to evaluate the midterm outcomes of aortic remodeling, clinical results, and reinterventions following the use of physician-modified endografts (PMEGs) in patients with post dissection thoracoabdominal aneurysms (PD-TAAAs). Methods: From January 1, 2017, to December 31, 2020, a cohort of 62 patients underwent fenestrated and branched endovascular aortic repair with PMEGs for residual type A and type B aortic dissection. The true lumen (TL) diameter and false lumen statues were assessed at four aortic levels. Data on aortic remodeling, survival rate, and reintervention were collected and analyzed. Results: Among the 62 patients treated with PMEGs, the overall survival rate and the freedom from reintervention were 94.5% and 79.4% at 5 years, respectively. The mean TL diameter at four levels before surgery was 27.09 ± 4.65 mm, 23.16 ± 5.58 mm, 18.04 ± 4.64 mm, and 15.41 ± 6.79 mm, respectively. The mean diameter of the TL at four levels after 1-year follow-up was 29.3 ± 4.92 mm, 27.47 ± 5.46 mm, 21.79 ± 3.62 mm, and 19.10 ± 4.41 mm, respectively, showing significant increase in TL diameter at all levels (P ≤ .05). The mean follow-up was 5.09 ± 0.71 years, with an overall survival rate of 96.4% (95% confidence interval [CI], 85.9%-99.1%) at 1 year and 94.5% (95% CI, 84.0%-98.2%) at 5 years. The freedom from reintervention rate was 92.7% (95% CI, 81.8%-97.2%) at 1 year and 79.4% (95% CI, 79.4%-96.0%) at 5 years. Conclusions: PMEGs for chronic dissection TAAAs can complete entry tears exclusion, resulting in satisfactory results. Aortic remodeling is favorable at the downstream aorta. Comprehensive pre-planning and strict follow-up protocol should be adopted to guarantee long-term outcomes.